2021
DOI: 10.3390/su132011192
|View full text |Cite
|
Sign up to set email alerts
|

Developing Eighth-Grade Students’ Computational Thinking with Critical Reflection

Abstract: As computer science has become a vital power in facilitating the rapid and sustainable development of various fields, equipping everyone with computational thinking (CT) has been recognized as one of the core pillars supporting the sustainable development of individuals and our digital world. However, it remains challenging for secondary school students to assimilate CT. Recently, critical reflection has been proposed as a useful metacognitive strategy for regulating students’ thinking to solve current and fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
(105 reference statements)
0
8
0
Order By: Relevance
“…Although Wei et al (2021) and Taylor and Baek (2019) found positive transfer outcomes, code writing and code reading were the underlying skills measured in the studies. Other studies adopted self-report instruments such as the CT-scale by Korkmaz et al (2017) in an investigation of the effects of critical reflection on middle schoolers’ CT skills (He et al, 2021). Whereas He et al (2021) found that students’ CT skills improved, the finding seems to equate CT disposition and self-beliefs to represent CT skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Wei et al (2021) and Taylor and Baek (2019) found positive transfer outcomes, code writing and code reading were the underlying skills measured in the studies. Other studies adopted self-report instruments such as the CT-scale by Korkmaz et al (2017) in an investigation of the effects of critical reflection on middle schoolers’ CT skills (He et al, 2021). Whereas He et al (2021) found that students’ CT skills improved, the finding seems to equate CT disposition and self-beliefs to represent CT skills.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies adopted self-report instruments such as the CT-scale by Korkmaz et al (2017) in an investigation of the effects of critical reflection on middle schoolers’ CT skills (He et al, 2021). Whereas He et al (2021) found that students’ CT skills improved, the finding seems to equate CT disposition and self-beliefs to represent CT skills. When CT is operationalized as programming or disposition, it may not be comparable with the result of CT as an instance of everyday problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating the fundamental concepts of CT in English writing enables the exercise of participants' critical thinking and develops a deeper understanding of complex issues [18,51]. The ability to think critically in writing is particularly important for sustainable development [6,18]. It enables students to effectively communicate their ideas, engage in constructive criticism, and work toward a sustainable world.…”
Section: Influence Of the Fundamental Concepts Of Ct In Improving Stu...mentioning
confidence: 99%
“…Computational thinking (CT) has been extensively integrated into the K-12 educational curriculum to establish a foundation for strong student performance and global sustainability in line with the Sustainable Development Goals for quality education [5,6]. Incorporating real-world applications and more hands-on project-based learning activities into the curriculum, and increasing technology use in the classroom can help K-12 students better understand the material and how it applies to their lives.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CT and critical thinking was examined to determine the criterion based validity of the developed CTS. Studies have reported that CT and critical thinking are interrelated (Buckley, 2012;Doleck et al, 2017;He et al, 2021). The Pearson product-moment correlation coefficient was measured to define the correlation between the scores from the CTS and MCTDS.…”
Section: Criterion Validitymentioning
confidence: 99%